(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Online Examination System is a web-based tool created to efficiently administer and oversee exams in a digital setting. Traditional pen-and-paper exams present many logistical difficulties, such as printing question papers, assigning invigilators, manually grading answer sheets, and managing results. This system is designed to remove these obstacles by offering an automated, easy-to-use platform that makes exam management simpler for both administrators and students. This project allows administrators to set up subjects, include multiple-choice questions, establish exams with defined time limits and grading rules, and oversee student records. Students are able to sign up, access their accounts, see which exams are available, and take part in them during a set period. The system instantly checks responses against the correct answers stored in the database and produces precise results, such as the total number of questions, correct answers, marks obtained, and whether the user passed or failed. Key components consist of user authentication, subject and question management, a real-time exam timer, automatic result generation, and comprehensive performance reports for both students and the admin panel. The system uses PHP and MySQL as its main technologies to ensure data integrity, security, and efficiency. This Online Examination System enhances the examination process by minimizing manual work, increasing the accuracy of results, and promoting transparency, making it a dependable and scalable solution for schools, colleges, and training institutes.